Analysis of Antihypertensive Drug Use in Pregnancy (Future Science, 2022)
The management of hypertension in pregnacy therapy aims to control the patient's blood pressure to the extent that it does not interfere with or damage other organ or physiological functions, reducing the risk of morbidity and mortality. The drugs used must be safe, effective and rational to achieve the desired therapy based on the high blood pressure experienced. The aim of this study was to analyze the use of antihypertensives in inpatient pregnancy at the Arifin Achmad Hospital, Riau Province, whether it was in accordance with the guidelines. The research method used a cross sectional study, data were taken using medical records and samples were taken by total sampling. Data taken from January 2019 to December 2021. The analysis was carried out descriptively. The results showed that out of 176 hypertensive patients in pregnancy, most were sin the age group of 21-35 years. The most common diagnosis was preeclampsia 90.9%. The most widely used antihypertensive by patients was a combination of Nifedipine and Methyldopa (64%). Most of the use of antihypertensive is in accordance with the guidelines (89.8%). In general, the use of antihypertensives in inpatient pregnancy at Arifin Achmad Hospital is in accordance with the guidelines. Proper management of hypertension will reduce morbidity and mortality.